GROWING STUDENTS’ WRITING FLUENCY USING FREE WRITING ACTIVITY - Dahlia, Anum (English Education Department of STKIP Pasundan, 2020)
For most EFL students especially novice writers, writing English was hard to do. They were often stuck with a lot of obstacles. The obstacles were not only about students’ knowledge in linguistic elements, such as grammar, structure, vocabulary, spelling, punctuation, capitalization but also about students’ attitudes toward writing. Writing was not easy and not fun for students. To solve this hardship, students required a particular activity which helped them improve their writing ability and change their attitudes. Free writing was the activity chosen to overcome this case. It was done in series over five times with time limit, and after that students did reflection on their five results of free writing. The purpose of this study was to examine the beneficial effects of using free writing activity toward students’ writing fluency and writing ability. The method used in this study was descriptive qualitative. This method described how effective free writing activity on students’ writing. Data were taken from students’ free writing samples as primary data, and the reflection as the secondary data. There were 75 free writing samples and 60 reflection samples. This study revealed that free writing made students get used to writing, improve linguistic elements, and be confident and comfortable in writing. Finally free writing gave beneficial effects for learners, it could make learners write more, write easier and write better.